(untitled) (Revista de Artes Marciales Asiáticas, 2021)
Thirty male senior kata athletes representing the karate styles Shotokan (n=10), Gojuryu (n=10) and Shitoryu (n=10), were recruited to verify their neuromuscular response to a simulated competition comprised of five different successive kata. They executed the medicine ball throw test and the countermovement jump test in two days, a control and a kata condition. For the upper-body muscle power, there was an effect of moment (F9,486 = 3.55, p ˂ 0001, ηp2 = 0.062, medium) with higher values pre 1 compared to pre 5 (p ˂ 0.001; d = 0.31, small). For the lower-body muscle power, there was a moment and condition interaction effect, with higher values pre kata 1 compared to pre kata 3 (p = 0.002; d = 0.34, small) and pre kata 5 (p ˂ 0.001; d = 0.41, small). Conversely, higher values post kata 5 compared to pre kata 5 (p ˂ 0.001; d = 0.31, small). There was no interaction among moment, style and condition. The kata simulated competition did not affected the upper-body power performance but the athletes started the third and fifth kata executions with reduced lower-body muscle power. Conversely there was an improvement in legs muscle power after kata 5 comparing to the pre kata 5. These results provide important information about the category and how the athletes are affected during a simulated competition.